Putative fossils of chemotrophic microbes preserved in seep carbonates from Vestnesa Ridge, off northwest Svalbard, Norway - Himmler, Tobias; Cremiere, Antoine; Birgel, Daniel; Wirth, Richard; Orphan, Victoria J.; Kirsimae, Kalle; Knies, Jochen; Peckmann, Jörn; Lepland, Aivo (Geology, 2021)
The microbial key players at methane seeps are methanotrophic archaea and sulfate-reducing bacteria. They form spherical aggregates and jointly mediate the sulfate-dependent anaerobic oxidation of methane (SD–AOM: CH4 + SO42– → HCO3– + HS– + H2O), thereby inducing the precipitation of authigenic seep carbonates. While seep carbonates constitute valuable archives for molecular fossils of SD–AOM-mediating microbes, no microfossils have been identified as AOM aggregates to date. We report clustered spherical microstructures engulfed in 13C-depleted aragonite cement (δ13C values as low as –33‰) of Pleistocene seep carbonates. The clusters comprise Mg-calcite spheres between ~5 μm (single spheres) and ~30 μm (clusters) in diameter. Scanning and transmission electron microscopy revealed a porous nanocrystalline fabric in the core area of the spheres surrounded by one or two concentric layers of Mg-calcite crystals. In situ measured sphere δ13C values as low as –42‰ indicate that methane-derived carbon is the dominant carbon source. The size and concentric layering of the spheres resembles mineralized aggregates of natural anaerobic methanotrophic archaea (ANME) of the ANME-2 group surrounded by one or two layers of sulfate-reducing bacteria. Abundant carbonate-bound 13C-depleted lipid biomarkers of archaea and bacteria indicative of the ANME-2-Desulfosarcina/Desulfococcus consortium agree with SD–AOM-mediating microbes as critical agents of carbonate precipitation. Given the morphological resemblance, in concert with negative in situ δ13C values and abundant SD–AOM-diagnostic biomarkers, the clustered spheres likely represent fossils of SD–AOM-mediating microbes.